Produção lacrimal induzida pela ciclosporina a e o tacrolimus em cães hígidos e com ceratoconjuntivite seca - Marconato, Francieli (2017)
Keratoconjunctivitis sicca (kCS) is a chronic inflammatory disease common in dogs, resulting from deficiency of the precorneal tear film. It can occur as a quantitative deficiency of the aqueous component of the tear, as well as a qualitative deficiency of the lipid or mucin components of the tear film, generating instability of that film. The ocular complications of this disease affect the ocular surface provoking vascularization, pigmentation and corneal edema. In more severe cases, it can also lead to loss of corneal epithelium, ocular pain and blindness. The treatment normally used for KCS is medicated and mainly includes tear, lacrimomimetics, mucolytics and topical antibacterials. Considering the importance of keratoconjunctivitis sicca, the objective of this study was to investigate and compare the treatment with different eye drops in healthy patients with KCS. For the study, a literature review on the KCS was carried out, addressing the main treatments (article 1), 13 dogs divided into two studies were used for the second study. The animals were divided into three groups of three animals each: in the CsA col group the treatment of the cornea was performed with cyclosporin A (0,05%) eye drops, Tacro group with tacrolimus eye drops (0,03%) and the CsA pom group with cyclosporin A ointment (0,05%). In the second study (article 3), the dogs were divided into two groups of two animals each, in the CsA col group collagen treatment was performed with cyclosporin A eye drops (0,05%) and the Tacro group with tacrolimus eye drops (0,03%). A drop of the medication was instilled every 12 hours in all animals and ophthalmic evaluations were performed on days 0, 15, 30, 45, 60, 75 and 90 days. Clinical signs of conjunctival hyperemia, type of present ocular secretion, corneal opacity, corneal vascularization and corneal pigmentation in healthy dogs and with KCS were evaluated through Schirmer's Lacrimal Test (TLS), Fluorescein Test, Rose Bengal Test. Based on the literature review on KCS, the best treatment described is tacrolimus eye drops. Among the surgical techniques, nasolacrimal duct occlusion was the best outcome. When analyzed the behavior of cyclosporin A in the formulation eye drops and ointment and tacrolimus in healthy animals, cyclosporin A in the ointment formulation was the one with the best lachrymal stimulation. In patients with CCS, when compared to treatments with CsA eye drops and tacrolimus, the dogs with tacrolimus were the most successful.